Design of Cloud-based and IPTV Digital Signage System - Algifanri Maulana; Asfiyan Asfiyan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The purpose of this research is to control, monitoring, and broadcast video, audio, text with digital signage system based on cloud and IPTV. It also provides multi content on one screen display included YouTube channel and RSS feed. Network connection transfer using internet protocol, the component of cloud-based and IPTV included with a content management system and a broadcast management system. Companies provide digital signage services are still using one of the ads in large size, this can alleviate the cost of advertising using digital signage. Therefore, the result is a designed from a display of how the content can be variatif when displayed on a digital signage as well through cloud-based and IPTV.